Unicystic ameloblastoma of the maxilla: A case report - Paikkatt V; Sreedharan S; Kannan V (Wolters Kluwer Medknow Publications, 2007)
Unicystic ameloblastoma is believed to be less aggressive and responds more favorably to conservative surgery than the solid or multicystic ameloblastomas. This report is a rare case of unicystic ameloblastoma of the maxilla that was treated by enucleation under suspicion of a radicular cyst related to a dens in dente. The neoplastic nature of the lesion became evident only when the enucleated material was available for histologic examination. With this report, the authors illustrate the importance and complexity of a differential diagnosis of lesions with a cystic aspect in the anterior region of the maxilla, among them - inflammatory radicular cysts, odontogenic keratocysts, adenomatoid odontogenic and unicystic ameloblastoma. Relevant diagnostic problems and choice of treatment of unicystic ameloblastoma are presented along with a review of the literature.